Aspek-Aspek Nilai Kebahasaan Jihad Dalam Pandangan Al-Qur,an - Bunyamin (STAIN MAJENE, 2019)
The interpretation of the verses of jihad, a few theories were found. First, ontologically, jihad can be divided into general and specific meaning. Generally speaking, jihad is all activities undertaken in earnest to uphold the good and resist damage in the midst of society. Meanwhile, in particular, jihad is a seriousness to defend the establishment of Islamic teachings on the battlefield. Second, epistemologically, the forms of jihad can be divided into jihad amwal and jihad anfus. Jihad amwal is the sacrifice of property to the maximum, both in connection with jihad in general or specifically. While jihad anfus is totality of the human soul is a sacrifice to defend the teachings of Islam, both in relation to jihad jihad in general or specifically. Third, axiologically, the implications of jihad can be distinguished on worldly and hereafter interests. In earthly life, the mujahid will always be guided by God for the right path and rewarded in kind, such as recognition, power, peace, and abundant sustenance.